The knights of Silversnow - Abbott, Tony.; Jessell, Tim (New York : Scholastic, 2002)
Eric, Neal, and Julie return to Droon to repair the damage they caused with the Wand of Urik and venture into a hidden castle in the snow-covered hills to wake up the legendary Knights of Silversnow, their last hope against Lord Sparr.
"A Little Apple paperback."
3.
007-010.
500
Accelerated Reader AR
Keywords: Droon (Imaginary place) -- Fiction; Fantasy fiction